Pengaruh Kreativitas Guru Pai Dalam Pembelajaran Terhadap Peningkatan Pemahaman Peserta Didik - M. Dahlan R; Abristadevi Abristadevi; Nuha Lutfiah Riyadi3 (Departement of Mathematics Education, 2023)
Teacher creativity is a way that can provoke the mindset of students combined with the problem solving method, the case study method which if we do in this learning will hone the mindset of students by developing their mindset to complete a case study and find solutions. This study aims to determine the influence of PAI teacher creativity in learning on increasing student understanding. This research was conducted in class XI-IPS SMAN 1 Bogor City with a total of 75 students. Data retrieval using Non-probability Sampling technique. Data collection using questionnaires developed in 30 statements. The validation test produces all 29 valid questions and 1 invalid question because the value obtained is at least 0.210 < 0.254. Reliability and Normality were performed with results of 0.735 and 0.200. The data is analyzed through product moment correlation with the help of SPSS.